Peningkatan Kompetensi Menyusun Laporan Keuangan bagi Koperasi Modern di Wilayah Kota Cimahi Jawa Barat - Hastuti Hastuti; Yanti Rufaedah; Mia Rosmiati; Benny Barnas; Ita Susanti; Deni Mulyana (Sam Ratulangi University, 2023)
Cooperative financial reports are one of the conditions for holding an Annual Member Meeting and issuing cooperative identification numbers for the realization of modern cooperatives. Cooperatives in the Cimahi City area have not all been able to fulfill these requirements. This community service program is aimed at increasing the competency of compiling financial reports for cooperative bookkeeping officers in the Cimahi City area which will be held in September 2022. The method of implementation is by compiling guidelines for preparing cooperative financial reports based on SAK ETAP and then delivering them by providing training and mentoring for 5 mixed day activities. The training materials consist of legal aspects of modern cooperatives, management of modern cooperatives and preparation of cooperative financial reports. The implementation of the activity took place at the TechnoPark Building, Cimahi City, West Java, which was attended by 23 participants as representatives of cooperatives in the Cimahi City area, whose data was obtained from the Department of Trade, Cooperatives, Small and Medium Enterprises, and Industry of Cimahi City. Based on the assessment of the results of the evaluation of training materials, there was an increase in understanding for the training participants and as many as 18 participants (78%) increased their competence by being able to complete accounting cases in preparing cooperative financial reports and by correcting their cooperative financial reports independently. Evaluation is also carried out on the success of the implementation of this program as a whole.